Erythrokeratoderma variabilis: Report of a case with rosette like lesions [Eritrokeratoderma variabilis: Rozet tipi lezyonlarla seyreden bir olgu] - (:unkn) unknown (My University, 2003)
Erythrokeratoderma variabilis (EKV) is a rare, autosomal dominantly inherited genodermatosis. The two distinct morphologic features of EKV are hyperkeratosis and transient erythema. Lesions appear during the first year of life and tend to follow a chronic course. We report a case of late onset EKV with rosette like skin lesions who responded well to the treatment with retinoids.
Keywords: Erythrokeratoderma variabilis; Isotretinoin